Utilizing analytical hierarchy process for pauper house programme in Malaysia - Mohamad, Mohd Sharif; Hasan Basari, Abd Samad; Hussin, Burairah (IJACS 2010, 2011)
In Malaysia, the selection and evaluation of candidates for Pauper House Programme (PHP) are done manually. In this paper, a technique based on Analytical Hierarchy Technique (AHP) is designed and developed in order to make an evaluation and selection of PHP application. The aim is to ensure the selection process is more precise, accurate and can avoid any biasness issue. This technique is studied and designed based on the Pauper assessment technique from one of district offices in Malaysia. A hierarchical indexes are designed based on the criteria that been used in the official form of PHP application. A number of 23 samples of data which had been endorsed by Exco of State in Malaysia are used to test this technique. Furthermore the comparison of those two methods are given in this paper. All the calculations of this technique are done in a software namely Expert Choice version 11.5. By comparing the manual and AHP shows that there are three (3) samples that are not qualified. The developed technique also satisfies in term of ease of accuracy and preciseness but need a further study due to some limitation as explained in the recommendation of this paper.